TANGGUNG JAWAB PIDANA DOKTER DALAM KESALAHAN MEDIS (Analisis Hukum Putusan Kasasi Nomor 365 K/Pid/2012) - Buamona, Hasrul (UIN Sunan Kalijaga Yogyakarta, 2014)
As with the case of dr.Dewa Ayu Sasiary Parwani et al suspected medical errors in medical action that causes the death of the patient has not been proven medical errors of aspects of medical disciplines that led to big problems due to the lack of evidence that proves the physician acts as a medical error. This research aims to find out how to determine if the criteria for a medical doctor suspected medical negligence, and whether the decision of the Supreme Court No. 365 K/Pid/2012 in accordance with the criminal liability of doctors in medical errors). (To determine the criteria for medical errors must first be proven by means of medical audit by the medical committee as stipulated in PERMENKES No. 755 of 2011 on the Implementation of the Medical Committee at the Hospital. Due to request criminal liability as a doctor in the decision of the Supreme Court 365K/Pid/2012 number, then the doctors who allegedly committed medical errors it should first be proven medical errors through medical audits conducted by the Medical Committee. If convicted of medical errors, the results of the audit can be used as a basis for law enforcement to determine fault in criminal law that a criminal can be held accountable